Congenital abnormalities and multiple sclerosis - Ramagopalan, S; Guimond, C; Criscuoli, M; Dyment, D; Orton, S; Irene M. Yee; Ebers, G; Sadovnick, D (BioMed Central, 2010)
Background: There is a strong maternal parent-of-origin effect in determining susceptibility to multiple sclerosis (MS). One hypothesis is that an abnormal intrauterine milieu leading to impaired fetal development could plausibly also result in increased susceptibility to MS. A possible marker for this intrauterine insult is the presence of a non-fatal congenital anomaly. Methods: We investigated whether or not congenital anomalies are associated with MS in a population-based cohort. We identified 7063 MS index cases and 2655 spousal controls with congenital anomaly information from the Canadian Collaborative Project on Genetic Susceptibility to MS (CCPGSMS). Results: The frequency of congenital anomalies were compared between index cases and controls. No significant differences were found. Conclusions: Congenital anomalies thus do not appear to be associated with MS. However, we did not have complete data on types and severity of congenital anomalies or on maternal birth history and thus this study should be regarded as preliminary.